2011
DOI: 10.1167/iovs.10-5536
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Adrenergic System in a Mouse Model of Oxygen-Induced Retinopathy: Antiangiogenic Effects of β-Adrenoreceptor Blockade

Abstract: This is the first demonstration that β-AR blockade is protective against retinal angiogenesis and ameliorates BRB dysfunction in OIR. Although the relevance of these results to infant ROP is uncertain, the findings may help to establish potential pharmacologic targets based on β3-AR pharmacology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
166
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(182 citation statements)
references
References 70 publications
14
166
0
2
Order By: Relevance
“…Both treatments normalised BP in diabetic Ren-2 rats; however, only ARB reduced retinal vasculopathy and improved the electroretinogram [24,38]. Similar comparisons in OIR may not necessarily be informative given that β-blockers have anti-proliferative effects in OIR [39], and whether this occurs by a BPdependent mechanism is uncertain as BP cannot be measured in P18 rodents. We therefore examined this question in normotensive mice with OIR, and our finding that aliskiren reduced neoangiogenesis and avascular retina in this model indicates that the beneficial effects of aliskiren on vasculopathy were not necessarily related to its antihypertensive properties.…”
Section: Discussionmentioning
confidence: 99%
“…Both treatments normalised BP in diabetic Ren-2 rats; however, only ARB reduced retinal vasculopathy and improved the electroretinogram [24,38]. Similar comparisons in OIR may not necessarily be informative given that β-blockers have anti-proliferative effects in OIR [39], and whether this occurs by a BPdependent mechanism is uncertain as BP cannot be measured in P18 rodents. We therefore examined this question in normotensive mice with OIR, and our finding that aliskiren reduced neoangiogenesis and avascular retina in this model indicates that the beneficial effects of aliskiren on vasculopathy were not necessarily related to its antihypertensive properties.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research studies performed in mice with oxygeninduced retinopathy (OIR), a worldwide used model for ROP (7), have demonstrated that norepinephrine accumulation and β-adrenoreceptor (β-AR) activation induce a HIF-1α-driven modulation of VEGF and IGF-1 and participate in mechanisms contributing to the shift from the avascular to the proliferative phase (8)(9)(10). Following these observations, two independent prospective pilot trials have demonstrated that oral propranolol administered to preterm newborns suffering from a precocious phase of ROP is effective in counteracting the progression of the disease (11,12), even though not sufficiently safe (11).…”
mentioning
confidence: 99%
“…Notably, in a mouse model of proliferative retinopathy, the pharmacological blockade of β-AR with propranolol has been demonstrated to reduce retinal levels of HIF-1α and, consequently, of proangiogenic factors (VEGF and IGF-1), markedly reducing retinal neoangiogenesis (35).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%